Capture the crown - Estep, Jennifer (Estep, Jennifer. Gargoyle queen novel., 2021)
A powerful mind magier and spy poses as a pampered princess to try to determine who is stealing royal tearstone, in the first novel of a new series set in the Crown of Shards world.